Biblionline Vol. 7, n.2 (2011) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
Biblionline Vol. 7, n.2 (2011)Link de acesso ao númerohttp://periodicos.ufpb.br/ojs2/index.php/biblio/issue/view/1002/showToc